2010
DOI: 10.1111/j.1600-0501.2010.02063.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the total lengths of abutment/implant assemblies generated with a function of applied tightening torque in external and internal implant-abutment connection

Abstract: Results from the present study suggested that to minimize the settling effect, abutment screws should be retightened at least twice at 30 N cm torque at a 10-min interval in all laboratory and clinical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 10 publications
2
53
1
1
Order By: Relevance
“…A cyclic loading test was performed to simulate oral mastication based on protocols established in earlier studies 8,14) . A cyclic loading test were performed for 10 6 cycles, which has been reported to produce results commensurate with 40 months of actual use 16) . Two loads, 100 or 300 N, were set considering that the average maximal posterior occlusal force for a fixed prosthesis supported by an implant has been reported to be between 35 and 330 N 17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cyclic loading test was performed to simulate oral mastication based on protocols established in earlier studies 8,14) . A cyclic loading test were performed for 10 6 cycles, which has been reported to produce results commensurate with 40 months of actual use 16) . Two loads, 100 or 300 N, were set considering that the average maximal posterior occlusal force for a fixed prosthesis supported by an implant has been reported to be between 35 and 330 N 17) .…”
Section: Discussionmentioning
confidence: 99%
“…Then, in addition to surface roughness, secondary factors such as the material, screw head, and thread design also have to be taken into consideration [5][6][7][8] . Furthermore, several other factors can exert a major influence on screw loosening, such as the structural design of the implant connection, a poor fit with an implant-supported prosthetic crown, and occlusal loading [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Some implants might have common technical failures including prosthetic screw loosening, implant or prosthetic fractures and micro-displacement of crowns and/or crown-implant connection [33,43,44]. These failures generally do not lead to implant loss, yet they represent a significant problem for clinicians and patients and result in additional costs.…”
Section: Implant Designmentioning
confidence: 97%
“…In this context, Kim et al [44] found that a hexagonal system has smaller seating in the platform junction compared to internal hexagon systems. Pessoa et al [6] compared the stress of the abutment screw connections between the external and internal hexagon, concluding that the stress was considerably higher in implants with an external hexagon.…”
Section: External Hexagonmentioning
confidence: 97%
See 1 more Smart Citation